Application of sensitivity theory to fuzzy logic based FDI - Dalton, Tracy; Klotzek, Petra; Frank, Paul M. (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes an application of sensitivity theory to the analysis of a certain class of fuzzy systems which can be used for fault detection and isolation (FDI). The work is divided into three main tasks. The first is the mathematical representation of some class of fuzzy systems. This is followed by an application of sensitivity theory to fuzzy systems based on the approach detailed in the first part.
Keywords: fuzzy systems; fault detection and isolation; fuzzy inference system; sensitivity theory; residual analysis; two-tank system